A Silk Fibroin Bio-Transient Solution Processable Memristor. Issue 1 (December 2017) - Yong, Jason; Hassan, Basem; Liang, You; Ganesan, Kumaravelu; Rajasekharan, Ranjith; Evans, Robin; Egan, Gary; Kavehei, Omid; Li, Jingliang; Chana, Gursharan; Nasr, Babak; Skafidas, Efstratios
Abstract Today's electronic devices are fabricated using highly toxic materials and processes which limits their applications in environmental sensing applications and mandates complex encapsulation methods in biological and medical applications. This paper proposes a fully resorbable high density bio-compatible and environmentally friendly solution processable memristive crossbar arrays using silk fibroin protein which demonstrated bipolar resistive switching ratio of 104 and possesses programmable device lifetime characteristics before the device gracefully bio-degrades, minimizing impact to environment or to the implanted host. Lactate dehydrogenase assays revealed no cytotoxicity on direct exposure to the fabricated device and support their environmentally friendly and biocompatible claims. Moreover, the correlation between the oxidation state of the cations and their tendency in forming conductive filaments with respect to different active electrode materials has been investigated. The experimental results and the numerical model based on electro-thermal effect shows a tight correspondence in predicting the memristive switching process with various combinations of electrodes which provides insight into the morphological changes of conductive filaments in the silk fibroin films.